PENGARUH TINGKAT LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA SUBSEKTOR MAKANAN DAN MINUMAN YANG TERCATAT DI BEI (BEI) PERIODE 2010-2017 - Andriani, Putri Rizki; Rudianto, Dudi (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
This study aims to determine the effect of the level of liquidity as measured by the Current Ratio, the level of profitability measured by Net Profit Margin and the level of leverage measured by the Debt to Asset Ratio effect on Company Value as measured by Price to Book Value in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) for the period 2010-2017. The analytical method used begins with descriptive analysis, model estimation, classical assumptions, multiple linear regression, coefficient of determination, then hypothesis. The results of this study indicate that the Current Ratio, Net Profit Margin and Debt To Asset Ratio significantly influence the Price To Book Value both partially and simultaneously. Judging from the magnitude of the regression coefficient Net Profit Margin is the largest, it means that the contribution of changes in the Net Profit Margin to Price to Book Value is the largest of the independent variables in this study. It is expected that the results of this study can be used as a reference for Investors in making investment decisions as well as for the Management of the Company to increase Company Value.